Answer:
Question (a)
Given equation:
![8^(2x) = 32^(x+3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/wo6k1x84d2ydbrf9e151yegpavya7q7sdj.png)
8 can be written as
![2^3](https://img.qammunity.org/2023/formulas/mathematics/high-school/x067ez1uo16vlr0h5f3y391xvlpksdp3g7.png)
32 can be written as
![2^5](https://img.qammunity.org/2023/formulas/mathematics/college/xbl83agl96twhuzheoqyzi1oll2btg8xqn.png)
Therefore, we can rewrite the equation with base 2:
![\implies (2^3)^(2x) = (2^5)^(x+3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/4mu3rblmrjwy84k3msruz1fia1bbngr001.png)
------------------------------------------------------------------------------
Question (b)
To solve:
![(2^3)^(2x) = (2^5)^(x+3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/yyam4fi3x1g24s7l555kniezrlttbu7tcr.png)
Apply the exponent rule
:
![\implies 2^(3 \cdot 2x) = 2^(5(x+3))](https://img.qammunity.org/2023/formulas/mathematics/high-school/5z80hpkgdpptuuuj7wjf0g5pnq4bk6mtg5.png)
![\implies 2^(6x) = 2^(5x+15)](https://img.qammunity.org/2023/formulas/mathematics/high-school/xqm58k3adfwgzdddwataa81ntahuc77sup.png)
:
![\implies 6x = 5x+15](https://img.qammunity.org/2023/formulas/mathematics/high-school/bhgi3yqg7pl7kpp42cl5d7ab4kbrxqej7u.png)
Subtract
from both sides:
![\implies x = 15](https://img.qammunity.org/2023/formulas/mathematics/high-school/2qhseh2yyagwelwzae97p5z27wewoncosa.png)